2021
DOI: 10.26434/chemrxiv-2021-w4sb3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fluorine labeling of ortho-phenylenes to facilitate conformational analysis

Abstract: ¹H NMR spectroscopy is a powerful tool for the conformational analysis of ortho-phenylene foldamers in solution. However, as o-phenylenes are integrated into ever-more-complex systems, we are reaching the limits of what can be analyzed by ¹H- and ¹³C-based NMR techniques. Here, we explore fluorine labeling of o-phenylene oligomers for analysis by ¹⁹F NMR spectroscopy. Two series of fluorinated oligomers have been synthesized. Optimization of monomers for Suzuki coupling enables an efficient stepwise oligomer s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The fluoro groups were included to help with the NMR analysis, as we have previously shown that 19 F NMR chemical shifts are sensitive to o-phenylene backbone conformations and can be used to detect and quantify the folding populations of different conformers, complementing 1 H-and 13 C-based spectra. 36 The methoxy groups along the backbone were included to ensure solubility; they were not exchanged late in the synthesis for the acetoxy groups used for the imines (Chart 1a) because it was not found to be necessary to improve folding. The seven different oligomers with different amide groups in Chart 1b were synthesized as described in Scheme S3.…”
Section: T H Imentioning
confidence: 99%
“…The fluoro groups were included to help with the NMR analysis, as we have previously shown that 19 F NMR chemical shifts are sensitive to o-phenylene backbone conformations and can be used to detect and quantify the folding populations of different conformers, complementing 1 H-and 13 C-based spectra. 36 The methoxy groups along the backbone were included to ensure solubility; they were not exchanged late in the synthesis for the acetoxy groups used for the imines (Chart 1a) because it was not found to be necessary to improve folding. The seven different oligomers with different amide groups in Chart 1b were synthesized as described in Scheme S3.…”
Section: T H Imentioning
confidence: 99%